Strategies for dynamic stability during adaptive human locomotion. - Patla, A.E (IEEE Engineering in medicine and biology magazine)
The focus of this article is how dynamic stability is achieved during locomotion adapted for complex environments that pose dangers to stability. Biped locomotion involves sudden transition from one support surface to another during every step. Therefore, control of legged locomotion, particularly stability, is difficult. We have discussed in detail the various strategies that are available to maintain balance during locomotion. Control of stability and hence locomotion is facilitated by the interplay between various strategies during adaptive locomotion. Sensory information from the three modalities (visual, vestibular, and kinesthetic inputs), knowledge, and prior experience all play a critical role in the control of dynamic stability. While much is known, many details remain to be filled in to complete our understanding of how dynamic stability is maintained during locomotion.